Resistência e cotidiano: o escravizado Leandro, seu crime e apelação no Tribunal da Relação no Recife (1851-1867). - Silva, José Anselmo da (2021)
This research deals with the historical daily life of the enslaved Leandro, by portraying some of his conquests and frustrations in Recife, the crime for which he was denounced in Magdalena's tavern and appealed to the Court of Appeal (1851-1867), resulting from the murder of black Jacinto of Nation. Likewise, through a booklet, it was possible to follow the roots, historical processes and part of the trajectory of this captive, which constitutes his survival strategies. In the methodological procedure, micro-history was used, following the example of Carlos Ginzburg, in reconstructing the common thread, which enables a greater understanding of the resistance to the institution of slavery, through the narrative of singular facts, as well as the use of technical procedures documents with a qualitative and bibliographic approach to the problem – concerns, alliances, behaviors and mistakes of those involved. Therefore, our sources are a cluster of laws, expertise, testimonies, reports from the Court and the Public Ministry, petitions, accusatory indictments, even if there is procedural fraud, sentences handed down by judges, judgment, appeal, newspapers found in Hemeroteca Digital, official letters in the House of Detention, bibliographical research of the scientific, social, political, temporal and spatial elements of this social phenomenon.